Global spatial data for agricultural GHG emissions and climate hazards - Safavi, Nina; Thornton, Philip K.; Wollenberg, Eva Karoline (Harvard Database, 2020)
Global spatial data for agricultural greenhouse gas (ghg) emissions and climate hazards